Towards the development of a fully protective Plasmodium falciparum antimalarial vaccine (2012)
If ever there were a truism then it would be that a completely protective Plasmodium falciparum malaria vaccine is desperately needed. Our institute has devoted all its efforts during the last 30 years to developing a fully protective, minimal subunit-based, multiepitope, multistage (targeting sporozoite and merozoite proteins), chemically synthesized antimalarial vaccine, given that peptides with high binding activity to their corresponding host cells (liver cells or red blood cells) form the springboard for vaccine design. However, such conserved high activity binding peptides have to be specifically modified to render them into highly immunogenic and protection-inducing peptides since they are immunologically silent. These modifications, analyzed at the 3D structural level by 1H-NMR, allow them a better fit into the MHC II-peptide-T-cell receptor complex to induce an appropriate immune response, providing a rational and logical approach (analyzed at the single atom level) for vaccine development, particularly in the field of malaria. © 2012 Expert Reviews Ltd.